Tourist satisfaction in the Malaysia tourism industry: Relationship between service innovation and destination image - Cheng, Boon Liat *; Shaheen, M.; Nor Khalidah, A.; Yap, C. S. (National University of Malaysia (UKM), 2020)
Malaysia has often been recognized by both local and international tourists as a premier visiting destination. Perception of a tourist destination, thus, has an important bearing on eventual tourist satisfaction. This study examines various aspects of service innovation that influence destination image in the Malaysian tourism industry. Data collected through self-administered questionnaires from 550 tourists using a convenience sampling approach were subjected to a reliability test, followed by multiple linear regression analysis to assess the proposed research hypotheses. The findings show that four variables of service innovation (product innovation, process innovation, organisational innovation and marketing innovation) were significantly and positively associated with destination image that, in turn, reflected tourist satisfaction. Nevertheless, the nationality of the tourist had a mediating effect on the relationship between destination image and tourist satisfaction. Tourism practitioners could benefit from these findings when the principles they espouse are applied to tourism management. At the same time, academic researchers would derive a better understanding of the factors that enhance destination image and, ultimately, tourist satisfaction.